History matters (?) Various Ways of Looking at History in Graham Swift’s Waterland - Loran Gami (American and British Studies Annual, 2018)
The paper focuses on how history is dealt with in Waterland, one of Graham Swift’s best-known novels. Even though the novel is not a pamphlet on the philosophy of history, it however explores the many ways in which history is indispensable for people in their endeavors to make sense of their past and their identity. However, Waterland presents different views of history and story-telling, which are often opposite and undermine one another. The paper will discuss how the novel, at times, suggests that tracing and reconstructing the past is a possible and objective activity, while, at other times, seeming to side with the idea that the past cannot be retrieved and that History is but an arbitrary ordering and construction of facts from the past, which are in themselves disorderly and structureless. In this regard, the novel has often been considered as taking part in the postmodernist debate about the truth in History. The article also deals with the contradictory perspective of History explored in Swift’s novel: that of History as a “Grand Narrative” of Progress and the opposite view of History as cyclical and regressive.